The effectiveness of national social dialogue institutions: From theory to evidence - Igor Guardiancich; Oscar Molina (International Labour Organization (ILO), 2020)
Social dialogue has been challenged in some countries in the wake of the Great Recession. In particular, National Social Dialogue Institutions (NSDIs) have sometimes been charged with having limited effectiveness in policymaking. This paper evaluates how and when NSDIs prove less effective than they should in performing their tasks, how to measure such effectiveness, and how to improve their operational capacity and impact. The effectiveness of social dialogue crucially depends on combinations of the problem-solving capacity of the NSDI, an encompassing mandate to deal with relevant socioeconomic issues and an enabling environment that grants the inclusion of social dialogue into decision-making. Combining the results from a 2017 ILO-AICESIS survey of Economic and Social Councils and Similar Institutions around the globe with the analysis of four case studies (Italy, South Korea, Brazil and Tunisia), the study shows substantial evidence that two sub-dimensions are key to enhance the policy effectiveness of NSDIs: enjoying political support and having an 'effective mandate' as opposed to relying on just a formal remit to deal with socioeconomic issues of interest.
Keywords: 330; social dialogue; tripartism